LOGO DESIGN BASED ON ARTIFICIAL INTELLIGENCE (AI) - Tuwio, Namuri Migo (DeKaVe, 2024)
The advancement of artificial intelligence (AI) has disrupted various aspects of human life, including the fields of art and design. This technology has proven to be a valuable tool in helping individuals create corporate identity designs (logos) quickly, cheaply, easily, and with a wide variety of options. Its open-source nature allows anyone, skilled or unskilled, to generate a logo without being bound by traditional, complex, and step-by-step methods. The continuous improvement of AI-based logo maker applications has the potential to shift the position of designers who tend to work with a “critical thinking dan creative thinking” approach. Based on this problem, this study aims to further interpret the collaborative process between humans and AI technology as a new creative achievement that can be accepted through academic and practical discussions. Using a practice-led research approach, the author explored various creative methods involving the collective work between designers and AI to produce a new logo design method that can broaden the practical and academic discourse. The theory of Posthumanism (AI Takeover) and the theory of Psychoanalysis (Four Discourses) were used as analytical tools to examine and reveal the potential of artificial intelligence (AI) as a creative instrument designing logo. Based on the study conducted, the method considered effective for designing logos based on artificial intelligence can be achieved through the following stages: 1. Research, 2. Formulating company values, 3. Writing (AI-Text Prompt), 4. Creating a Logo with an AI Application, 5. The logo generated by AI is used as a reference for conventional design, 6. Logo Selection and Adjustment, 7. Developing philosophical meaning, 8. Testing, 9. Evaluation (Improvement/Finalization). In addition, human intervention (designer) is still needed to make the logo by the automation machine able to requirements as a work of art. Furthermore, this study also clarifies the position of artificial intelligence (AI) technology as a tool created to encourage designers into “posthuman beings” with new competencies/abilities in creating works (designing logo).